Clinical and Radiographic Outcomes After Arthroscopic Iliac Bone Grafting for Traumatic Anterior Shoulder Instability with Significant Glenoid Bone Loss – A Minimum of Five-year Follow-up. Issue 7 (31st July 2020) - Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuke; Tokai, Morihito; Takeuchi, Yasutaka; Morioka, Takeshi; Kamijo, Hideki; Hoshika, Shota; Ueda, Yusuke
Objectives: The choice of surgical options for traumatic anterior shoulder instability with severe glenoid bony defect remains controversial. The purpose of this study was to evaluate the outcomes after arthroscopic (AS) iliac grafting with capsulolabral reconstruction with a minimum of five-year follow-up. Methods: Subjects consisted of 24 patients (24 shoulders), including 22 males and 2 females, who underwent AS iliac bone grafting and were followed for more than five years. Eighteen shoulders were primary surgery, and 6 were revision surgery. The mean age at surgery was 30 years (range, 18-52), and the mean follow-up was 8 years (range, 5-11). The mean glenoid bony defect measured on preoperative 3D-CT was 22% (range, 20-28). All surgeries were performed under general anesthesia. Free bone graft with approximately 2.0 cm length and 0.8 cm height was harvested from the iliac crest with the patients in the supine position, (Figure 1) and then the patient was placed in the beach chair position. The bone graft was inserted in the glenohumeral joint and arthroscopically fixed to the anterior glenoid using 2 cannulated screws followed by soft tissue Bankart repair using four anchors. (Figure 2 Gr: graft GL: glenoid) Functional outcomes including Rowe score, sports return, and ROM were evaluated. Radiographic findings including Samilson osteoarthritis (OA) grade and graft evaluation using 3D-CT at the final follow-up were also evaluated. Results: No patients experienced re-dislocation after surgery except one patient. All patients returned to their sports after surgery except for one patient who was not engaged in any sports. The mean Rowe score improved significantly from 19 (range, 5-40) to 95 (range, 70-100) (p<.0001). Postoperative forward flexion showed significant improvement: 157 (range, 110-180) to 170 (range, 150-180) degrees (p=.006), but no improvement in external rotation: 56 (range, 30- 85) to 56 (range, 30-70) degrees, and internal rotation: T8 (range, T5-L5) to T10 (range, T7-L5) level. OA change progressed in 8 shoulders (40%). 3DCT at the final follow-up demonstrated remodeling of the graft in 20 shoulders (88%) and absorption in 3 shoulders (12%).Failure case: A 23-year-old male experienced re-dislocation of the left shoulder during snowboarding five-year after the index surgery. Healed graft fracture and screw breakage were confirmed on 3DCT images (Figure 3). Conclusion: AS iliac bone grafting for traumatic anterior shoulder instability with significant glenoid bone loss yielded a satisfactory outcome with a minimum of five-year follow-up. Although this is technically demanding procedure, AS iliac bone grafting with capsulolabral reconstruction for shoulders with severe glenoid bone loss is an effective and practical procedure. Figure 1. Figure 2. Figure 3.